Hybrid Marketing Strategy Analysis at Danau Toba International Hotel Medan Using IFAS–EFAS - Novita Indah Ruth Lestari Pasaribu; Endang Sulistya Rini; Nisrul Irawati (Mandalika Journal of Business and Management Studies, 2026)
Digital transformation in the hospitality industry has significantly reshaped marketing practices; however, many hotels continue to rely heavily on conventional promotional methods. Danau Toba International Hotel Medan, a long-established star-rated hotel that accommodates various meetings and events, recorded a Room Occupancy Rate (ROR) of 32.2% during the January–June 2025 period, substantially below the industry benchmark. This study aims to analyze the hotel's marketing performance through the integration of digital and conventional marketing approaches using IFAS–EFAS analysis and to formulate a hybrid marketing strategy to improve occupancy rates. The study employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews with the Sales Manager, Front Office Manager, and Marketing personnel. Supporting data were obtained from direct observations, internal documents, and booking reports from 2023 to 2025. The analysis was conducted using SWOT analysis supported by the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) frameworks. The findings indicate that the low occupancy rate was primarily attributable to limited utilization of digital marketing, inconsistent online campaigns, and a continued reliance on conventional marketing methods. The IFAS analysis produced a score of 3.20, indicating a strong internal position, while the EFAS analysis generated a score of 2.88, reflecting a moderately favorable external environment. The hotel was positioned in Quadrant IV (Grow and Build), indicating the need for a balanced enhancement of its marketing strategy. The resulting Hybrid Marketing Integration Model (HMIM) emphasizes the importance of optimizing Online Travel Agents (OTAs) and social media platforms, strengthening corporate sales activities, improving digital marketing competencies among human resources, maintaining content consistency, and enhancing interdepartmental coordination efficiency.